2008
DOI: 10.1002/ijc.23350
|View full text |Cite
|
Sign up to set email alerts
|

17β‐hydroxysteroid dehydrogenase Type 1, and not Type 12, is a target for endocrine therapy of hormone‐dependent breast cancer

Abstract: Oestradiol (E2) stimulates the growth of hormone-dependent breast cancer. 17b-hydroxysteroid dehydrogenases (17b-HSDs) catalyse the pre-receptor activation/inactivation of hormones and other substrates. 17b-HSD1 converts oestrone (E1) to active E2, but it has recently been suggested that another 17b-HSD, 17b-HSD12, may be the major enzyme that catalyses this reaction in women. Here we demonstrate that it is 17b-HSD1 which is important for E2 production and report the inhibition of E1-stimulated breast tumor gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
101
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(107 citation statements)
references
References 48 publications
5
101
1
Order By: Relevance
“…RT-PCR analysis of LNCaP mRNA indicated that the wild type cells from this laboratory has shown that it is unable to mediate this reaction (Day et al, 2008b). Instead it is thought to be involved in the metabolism of fatty acids (Moon & Horton, 2003).…”
Section: -Hsd3 Inhibition 19mentioning
confidence: 97%
See 1 more Smart Citation
“…RT-PCR analysis of LNCaP mRNA indicated that the wild type cells from this laboratory has shown that it is unable to mediate this reaction (Day et al, 2008b). Instead it is thought to be involved in the metabolism of fatty acids (Moon & Horton, 2003).…”
Section: -Hsd3 Inhibition 19mentioning
confidence: 97%
“…At present, none of these inhibitors has reached clinical trial, and only recently has efficacy been demonstrated in vivo for the first of the enzymes, 17-HSD1, in models of breast cancer (Day et al, 2006b;Husen et al, 2006;Day et al, 2008b).…”
Section: Development Of the In Vitro Proof Of Concept Modelmentioning
confidence: 99%
“…The enzyme catalyses both oxidative (17-hydroxy to 17-keto) and reductive (17-keto to 17-hydroxy) 17b-HSD activity with a proper cofactor added in vitro. However, in cultured cells, the h17 -HSD1 has been shown to catalyse predominantly the reductive reaction [247]. Although h17 -HSD1 expression in various peripheral tissues is low, its catalytic efficacy is markedly higher than those measured for 17 -HSD7 and 17 -HSD12 [248,242], suggesting an important role for 17 -HSD1 in peripheral E2 formation.…”
Section: β -Hydroxysteroid Dehydrogenase and Pregnancy -Role Of 11bmentioning
confidence: 98%
“…5α-reductase inhibitors. [17][18][19][20] Although a number of steroidal and nonsteroidal inhibitors of 17β-HSD1 [21][22][23] are described and there is experimental evidence for the effectiveness of 17β-HSD1 inhibition against human tumor cell lines in vitro and in animal models, there is no inhibitor under clinical evaluation. Moreover, no proof of principle study in an animal disease model has been conducted for the indication endometriosis, although this is a widespread disease for which no adequate medical treatment is available.…”
Section: Figurementioning
confidence: 99%